Theriogenology (IntechOpen, 2025)
This book brings important insights into advances in knowledge related to production, companion or wild animals, highlighting state-of-the-art technology, challenges and perspectives of applying appropriate reproductive management and innovative technologies for animal production, reproductive control or the conservation of genotypes of interest.It is divided into four major sections: reproductive physiology, reproductive pathology, assisted reproduction, and animal breeding. The first, on reproductive physiology, comprises chapters on the autonomous innervation of the male gonad, steroidogenesis, sperm physiology and ovulation mechanisms. The second section, on reproductive pathologies, highlights review studies on endometritis, postpartum anestrus and disorders in sexual development. The following section is dedicated to assisted reproduction, being focused on biobanking sperm and somatic tissues, as well as in vitro embryo production. Finally, the last section is dedicated to animal breeding, presenting chapters concerning this theme for both domestic and wild species.